1962
DOI: 10.1364/ao.1.000033
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for an Electron Accelerator Using an Optical Maser

Abstract: Among many possible applications of the extremely high brightness temperature and the radiation density obtainable with the optical maser, a high energy electron accelerator is proposed and discussed in this paper. It consists of a cylindrical tube of maser material excited by a pumping radiation through an interference filter coated on its outer surface and, it generates an oscillation in a TMoNM type mode. An optical peak power of 10 kw/cm 2 was calculated to accelerate electrons by 109 ev/meter. A gasfilled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

1980
1980
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(45 citation statements)
references
References 1 publication
0
44
0
1
Order By: Relevance
“…The idea of using lasers to accelerate particles was first proposed by Shimoda [21] and others in the 1960's, while lasers themselves were still in their infancy. It was not until much later that the first experiments demonstrating acceleration of electrons with light appeared.…”
Section: Prior Experiments In Laser Accelerationmentioning
confidence: 99%
“…The idea of using lasers to accelerate particles was first proposed by Shimoda [21] and others in the 1960's, while lasers themselves were still in their infancy. It was not until much later that the first experiments demonstrating acceleration of electrons with light appeared.…”
Section: Prior Experiments In Laser Accelerationmentioning
confidence: 99%
“…Here, we mainly concentrate on Potassium Dihydrogen Phosphate (KDP), a negative uniaxial crystal commonly used for frequency multiplication of Nd:YAG lasers 3 . In this case, phase matching can be achieved for parallel beams 2 We do not intend this technique as a route for Fast Ignition since the spectrum of the ions is too energetic once the RPD regime is operational. 3 In the rest of the paper we assume for KDP the following Sellmeier's equations: ("collinear geometry") when the pump beam is at an angle θ m with respect to the KDP optical axis:…”
Section: Opcpa Pulse Compressionmentioning
confidence: 99%
“…Although the potential of lasers for particle acceleration was yet recognized in the early 1960's [1], research over the past 50 years has shown that developing an effective laser acceleration scheme is not straightforward. In the explosion-like interaction of tightly focused ultra-intense laser pulses with matter, electrons are violently expelled out of the focal region and are effectively accelerated only over short distances, typically comparable to the dominant wavelength of the pulse spectrum.…”
Section: Introductionmentioning
confidence: 99%